2019
DOI: 10.1002/admt.201900554
|View full text |Cite
|
Sign up to set email alerts
|

Laser Programmable Patterning of RGO/GO Janus Paper for Multiresponsive Actuators

Abstract: ease of preparation. As a pioneer of this field, Gracias' group has proposed several impressive bilayer actuators. For instance, a thermoresponsive theragripper with photopatternable poly(propylene fumarate) (PPF)/poly(N-isopropylacrylamide-coacrylic acid) (pNIPAM-AAc) bilayer structure has been developed for drug delivery. [28] Besides, Yang and co-workers have successfully fabricated stimuliresponsive actuators including an intelligent spring, a smart gripper, and a new type of "microrobot" based on the sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 40 publications
0
36
0
Order By: Relevance
“…developed a tape/RGO/GO actuator-based smart curtain by the binary cooperative complementarity ( Figure 8 A). 126 As shown in Figure 8 B, the tape/RGO/GO actuators bend to the GO side under light and electricity stimuli because of a large CTE mismatch between the tape layer (≈137 ppm K −1 ) and the GO layer (0.85 ppm K −1 ). 146 Tape/RGO/GO actuators bend to the tape side under moisture stimuli because the tape is inert to moisture, and the GO layer expands by absorbing water molecules.…”
Section: Mechanismsmentioning
confidence: 98%
See 1 more Smart Citation
“…developed a tape/RGO/GO actuator-based smart curtain by the binary cooperative complementarity ( Figure 8 A). 126 As shown in Figure 8 B, the tape/RGO/GO actuators bend to the GO side under light and electricity stimuli because of a large CTE mismatch between the tape layer (≈137 ppm K −1 ) and the GO layer (0.85 ppm K −1 ). 146 Tape/RGO/GO actuators bend to the tape side under moisture stimuli because the tape is inert to moisture, and the GO layer expands by absorbing water molecules.…”
Section: Mechanismsmentioning
confidence: 98%
“… 50 Meanwhile, laser technologies are capable of high-efficiency, mask-free patterning, and hierarchical structuring of graphene, which is of benefit to the design and fabrication of electrothermal actuators. As typical examples, RGO- or LIG-based electrothermal actuators, including LRGO/PI, 122 Ag-LRGO/PI, 123 LRGO/polyethylene (LRGO/PE), 124 PI/LIG/PVDF, 125 GO/RGO/tape, 126 and PI/LIG/PDMS 39 structures have been successfully developed, demonstrating sophisticated deformation ability. The hierarchical structure of graphene plays an important role for the performances of ERAs.…”
Section: Mechanismsmentioning
confidence: 99%
“…12e and f). Based on the property of anisotropic water-molecule adsorption for smart actuators, there are also some reports that further explored the gradient reduction of graphene oxide to obtain anisotropic Janus GO/RGO paper, such as laser interference 260,261 or laser writing, 262 reductions triggered by different reduction and oxidation properties, 263 unilateral ultraviolet (UV) irradiation, 264 chemical reduction with hydriodic acid (HI) 265 and others. 266 Among them, compared with laser writing and sunlight irradiation, Han and co-workers 264 further found that UV is conducive to the large-scale, efficient, and simple production of bilayer GO/RGO paper with a more uniform structure, resulting in a stable response and performing complex actions after external stimuli.…”
Section: Inorganic Papermentioning
confidence: 99%
“…[81] Laser processing can produce various precise and detailed patterns, which has been widely applied to various samples with wide applications, such as surface-enhanced Raman scattering substrates, power generators, supercapacitors, sensors, and actuators. [82][83][84][85][86][87][88][89][90][91] Line-by-line scanning and point-by-point ablation can both be realized by adjusting the scanning speed. Line-by-line scanning is widely used to produce separate microgrooves or homogeneous large-area coarse surfaces.…”
Section: Laser Processingmentioning
confidence: 99%